Preventive effects of systemic Pistacia eurycarpa Yalt. administration on alveolar bone loss and oxidative stress in rats with experimental periodontitis - Mustafa Atalay; Mustafa Özay Uslu; Mehmet Sina İçen; Nuray Üremiş; Yusuf Türköz (University of São Paulo, 2024)
Abstract Objective: This study aimed to investigate the effects of systemic administration of P. eurycarpa Yalt. plant extract on alveolar bone loss and oxidative stress biomarkers in gingival tissue in a rat model of experimental periodontitis. Methodology: 32 male Wistar albino rats, weighing 200-250 g, were divided into four groups (n=8): Healthy control (HC), Experimental periodontitis control (EPC), Experimental periodontitis 400 mg/kg (EP400), Experimental periodontitis 800 mg/kg (EP800). Experimental periodontitis was induced using the ligating method. Distilled water was administered to the HC and EPC groups and the plant extract was administered to the EP400 and EP800 groups by oral gavage at doses of 400 mg/kg and 800 mg/kg, respectively. The rats were sacrificed on the 15th day. The values of glutathione peroxidase GSH-Px, malondialdehyde (MDA), superoxide dismustase (SOD), interleukin-1β (IL-1β), interleukin-10 (IL-10), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI) in the gingival tissues were analyzed by ELISA tests. Alveolar bone loss was assessed using micro-CT images of the maxilla. Results: Although the IL-1β, TOS, OSI results of the healthy control group were lower than those of the other groups, the TAS values were higher (p<0.05). No significant difference was found in the biochemical parameters among the EPC, EP400, and EP800 groups (p>0.05). Alveolar bone loss was significantly reduced in the extract groups compared to the EPC group (p<0.001). Conclusion: Within the limitations of this study, it was observed that the systemic P. eurycarpa extract application reduced alveolar bone loss in a rat model of experimental periodontitis. Further studies are needed to elucidate the beneficial effects of P. eurycarpa.